Aceptabilidad sensorial y actividad antimicrobiana de aceites esenciales sobre bacterias contaminantes y patógenas de pure de tomate - Sajur, Silvia Analia (2014)
The new trend in food industry, preferred by consumers, is the use of natural preservatives toreplace traditional methods. Investigations are being oriented on the application of new methodsof making food safe which have a natural or ?green? image. Application of essential oils (EOs) isa very attractive method for controlling postharvest diseases and spoilage in various fruits andvegetables. In a previous work we isolated and identified Klebsiella ornitolytica and Candidatropicalis from tomatoes surface. In addition we demonstrated that Escherchia coli was able togrowth in tomato puree during storage at 30ºC. So, the aim of this work was to test andcompare the antimicrobial activities of four EOs against undesirable bacteria and yeasts isolatedtomatoes and obtained from collection cultures. Inhibition of growth by different concentration(50-300 ppm) of EO from lemon(Citrus limon), oregano(Origanum vulgare L.), onion (Alliumcepa) or garlic(Allium sativum) was tested by the paper disc agar diffusion method. First, thesensory acceptability of the EOs was evaluated in tomato purée (TP) by an untrained panelusing a hedonic scale of four points. Lemon essential oil was the most acceptable for all thedifferent concentrations tested except 300 ppm. Contrary, onion essential oil was not acceptableunder any condition. Garlic essential oil did not show antibacterial activity, being only activeagainst the Candida tropicalis. The growth of all tested microorganisms, E. coli ATCC 25922,Klebsiella ornitholytica, Listeria monocytogenes and C. tropicalis were inhibited by lemon andoregano essential oils at 300 ppm, which was considered unacceptable from view pointsensorial. In this condition, oregano essential oil was the most effective, producing inhibitionzones between 12 and 27 mm. Lemon essential oil was the only one capable of inhibit thegrowth of E .coli ATCC 25922, K.ornitolytica and L. monocytogenes at lower concentrations(150-200 ppm). At these concentrations the organoleptic contribution of lemon EO to the flavorwas satisfactory. In conclusion, lemon, oregano and garlic Eos showed promising results,especially lemon EO for the utilization of as suitable preservative agent for use inminimallyprocessed fruit products.